LEADERS' BEHAVIORAL REPERTOIRE AND ITS ROLE ON REDUCING DEFEATIST ORGANIZATIONAL BEHAVIOR IN WORKPLACE - Dr. Hamed Adel Abbas Al-Nasrawi; Mohammed Hameed Yasir (Scholars Digest Publishing, 2023)
This research examines the nature of relationship between behavioral repertoire and defeatist organizational behavior in the Kufa Cement Factory in Najaf, as its importance is represented in dealing with two very important variables in organizational environment, as well as appropriate foundations to address a realistic problem that directly affects work environment on one of the most important Iraqi institutions, so researcher used the random sampling method to distributed 120 questionnaires to many workers in the aforementioned factory, both men and women. (112) valid questionnaires were used for statistical analysis, and both advanced statistical software (SmartPLS4) and statistical software (SPSS) were used. Theoretical findings indicated that more research is needed to fully understand the connection between behavioral repertoire and defeatist organizational behavior in the factory, while practical findings indicated that the behavioral repertoire has a positive and significant influence on this type of behavior.
Keywords: Behavioral Repertoire, Defeatist Organizational behavior, Competitive Role.